CONTRIBUTION OF MOTHER’S KNOWLEDGE ABOUT TECHNOLOGY TRANSFER OF FOOD UNIFICATION AS SUPPLEMENTS ON CHILDREN - wahyuningrum, Ari Damayanti; Satiti, Ika Arum Dewi (Institute for Research and Community Service, Health Polytechnic of Kerta Cendekia, Sidoarjo, 2023)
The manifestation of human resources begins in the womb until the first 1000 days of life. Increased nutritional needs in the body that are not met while in the womb can result in various nutritional problem such as low birth weight, malnutrition, iron deficiency. The completeness of nutritional elements in food is often experienced by toddlers as having an impact on stunting, one of the influencing factors is the mother’s knowledge about the nutritional adequacy of toddlers and how to process food as Makanan Pendamping Air Susu Ibu (MPASI, weaning food) ingredients. The most common commodities in Srigonco village are green bananas, tuna, and red spinach but these commodities are sold at the Bantur market and families only eat rice, salt and crackers. In April 2023 survey through cadres, there were 30 stunted children. The solution offered is in the form of training, mother’s assistance for 3 months in making daily food menu variants using natural ingredients in Srigonco village with the combination of green bananas, tuna, and red spinach as MPASI which are adapted to the child age group. The service implementation procedure provides training and assistance to mothers who have stunted children and are at risk of stunting.